Innovation in the creative industries: Linking the founder's creative and business orientation to innovation outcomes - Florian Koch; Max Hoellen; Elmar D. Konrad; Alexander Kock (Creativity and Innovation Management, 2023)
Creative industries contain paradoxes because conflicting tensions arise between the market and the arts. Entrepreneurs need to find and maintain a balance between those two sides to create innovation. This study tests the interaction between business and creative orientations of a founder in their influence on innovation in the context of creative entrepreneurial firms and provides recommendations for how creative agents can leverage and manage their innovations based on their creative visions. Determinants on the individual level, such as the founder's creative or business orientations, have a lasting impact on the practices and process of their venture. To trace the imprinting influence of the founder's orientation on innovation, the empirical setting is a time-lagged study of German firm owners in the cultural and creative industries surveyed 50.167emyears apart. The results show a significant relationship between creative orientation and innovation, whereas business orientation does not significantly relate to innovation. However, creative and business orientations reveal a negative interaction effect. This study contributes empirical evidence to the paradox theory and the interaction between the opposite poles. Our findings provide valuable insights about the relevance of creative orientation and its visionary impact on the firms' innovation process. Furthermore, the results shed new light on the tension between art and the market, as different compositions of the two orientation poles seem to have a varying impact on the degree of innovation. Thus, the study reveals the complexity of creative entrepreneurship and provides managerial guidance for other knowledge-based industries.
Keywords: 330; creative and business orientation; creative industries; innovation; paradox theory; tensions